2003
DOI: 10.1145/602421.602422
|View full text |Cite
|
Sign up to set email alerts
|

The decay and failures of web references

Abstract: Attempting to determine how quickly archival information becomes outdated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
100
0
6

Year Published

2005
2005
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 10 publications
15
100
0
6
Order By: Relevance
“…Moreover, with the vast quantity and easily accessible documentation available on the Web, many authors often cite Uniform Resource Locators (URLs) as part of the attribution process when it comes to acknowledging supporting material in their publications (Germaine 2000;Rumsey 2002;Spinellis 2003).…”
Section: The Url As An Information Resource Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, with the vast quantity and easily accessible documentation available on the Web, many authors often cite Uniform Resource Locators (URLs) as part of the attribution process when it comes to acknowledging supporting material in their publications (Germaine 2000;Rumsey 2002;Spinellis 2003).…”
Section: The Url As An Information Resource Referencementioning
confidence: 99%
“…As the amount of available information has increased via the Web, so has the corresponding use of citations to Web-located sources by writers of reports and scholarly works (Spinellis 2003). Indeed, the permanency of these cited Web resources has been questioned by various authors, with disappearance rates of cited Uniform Resource Locators (URLs) for scholarly journal articles having been reported (Germaine 2000;Lawrence et al 2001;Rumsey 2002;Spinellis 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a 2003 study of Internet ci-tations in three major scientific and medical journals revealed that 27 months after publication, the proportion of inactive links rose to 13 per cent (Dellavalle, et al, 2003). The exact proportions differ, but similar results have been noted for Web-citations in other biomedical journals (Hester, et al, 2004;Crichlow, Davies & Wimbush, 2004;Wren, 2004), in computer science journals and conferences (Spinellis, 2003;Selitto, 2005), and the informetrics sub-discipline of information science (Bar-Ilan & Peritz, 2004).…”
Section: Introduction *mentioning
confidence: 86%
“…We are all familiar with the link failure syndrome that plagues the Web. Spinellis 1 indicates that approximately 28% of the URIs referenced in Computer and Communications of the ACM articles between 1995 and 1999 were no longer accessible in 2000 and the figure increased to 41% in 2002. Some scholars 2 have asked rhetorically, "How confident can we be when an object whose authentication is crucial depends on electricity for its existence?…”
Section: Introductionmentioning
confidence: 99%